Pengaruh unsur Tembaga (Cu) terhadap fluiditas paduan Al-Si 11.8 wt% (ADC 12) dengan metode Vacuum Suction Test - Suharno, Bambang; Nanda, Is Prima; Arifin, Bustanul; Seto, Demas (Jurnal Energi Dan Manufaktur; Vol 1, No.2 Desember 2006)
Al-Si 11.8 wt% alloy which classified to eutectic Al-Si composition usually used to produce a flat casting product with high pressure die casting process. Alloying element become an important things to determine behavior and characteristic of aluminum. Copper added into aluminum to improve strength and hardness, but there has no many studies on the effect of copper on fluidity. This fluidity study is using vacuum suction test method and the microstructure is observed with SEM/EDS. Spectrometer test has been used to find out chemical composition of sample. The result of this study shows that with copper addition from 2.25 wt% to 3.11 wt%, the fluidity value has increased 24.11% on 680oC pouring temperature. On 3.11 wt% copper composition, fluidity value has increased 14.38% from 640oC pouring temperature to 700oC pouring temperature.
Keywords: aluminum alloy, fluidity, copper, vacuum suction test